EFEKTIVITAS PENAMBAHAN TRIPTOFAN PADA PAKAN KOMERSIL UNTUK MENEKAN TINGKAT KANIBALISME UDANG VANAME (Litopenaeus vannamei) - Dhea Salsa Ardina; Supono Supono; Limin Santoso (Jurnal Akuakultur Rawa Indonesia, 2021)
The obstacle in vaname cultivation is the high death rate due to cannibalism. The effort that can be done is giving tryptophan. Tryptophan as serotonin synthesis in the brain so that it helps suppress the level of aggressiveness thereby reducing shrimp cannibalism. The purpose of this study was to analyze the level of cannibalism, growth and survival of vaname shrimp fed tryptophan in feed, and to determine the optimal dose in the addition of tryptophan to comercial fed. Design in this research used a completely randomized design consisting of 3 treatments and 4 replications: (A) Control (without tryptophan), (B) 1,0% tryptophan/kg feed, (C) 1,5% tryptophan/kg feed. Parameters observed were cannibalism rate, absolute weight growth, survival rate, feed conversion ratio and water quality. The results showed that the addition of tryptophan to commercial feed had a significant effect (P?0.05) on each treatment. Treatment C, which is the addition of 1,5% tryptophan, is the most optimal treatment where the vannamei shrimp cannibalism rate has the lowest value of 2,50%, absolute weight growth of 0,38 grams, survival rate of 94%, and feed conversion ratio of 0,50. Water quality parameters are in a good range for vaname shrimp culture. Key words : canibalism, tryptophan, Vannamei shrimp